Blue-shift photoconversion of near-infrared fluorescent proteins for labeling and tracking in living cells and organisms - Francesca Pennacchietti; Jonatan Alvelid; Rodrigo A. Morales; Martina Damenti; Dirk Ollech; Olena S. Oliinyk; Daria M. Shcherbakova; Eduardo J. Villablanca; Vladislav V. Verkhusha; Ilaria Testa (Nature Communications, 2023)
Abstract Photolabeling of intracellular molecules is an invaluable approach to studying various dynamic processes in living cells with high spatiotemporal precision. Among fluorescent proteins, photoconvertible mechanisms and their products are in the visible spectrum (400–650 nm), limiting their in vivo and multiplexed applications. Here we report the phenomenon of near-infrared to far-red photoconversion in the miRFP family of near infrared fluorescent proteins engineered from bacterial phytochromes. This photoconversion is induced by near-infrared light through a non-linear process, further allowing optical sectioning. Photoconverted miRFP species emit fluorescence at 650 nm enabling photolabeling entirely performed in the near-infrared range. We use miRFPs as photoconvertible fluorescent probes to track organelles in live cells and in vivo, both with conventional and super-resolution microscopy. The spectral properties of miRFPs complement those of GFP-like photoconvertible proteins, allowing strategies for photoconversion and spectral multiplexed applications.